(untitled) (Bulletin of the International Association for Paleodontology, 2020)
Aims. Compared to occlusal dental wear, labial/buccal abrasion is seldom documented in prehistoric groups. This type of wear occurs in some ethnographic-present and living populations and leaves telltale facets on non-occlusal vestibular surfaces associated with labrets. Methods and materials. For detailed macroscopic, microscopic (binocular and SEM) and thin-sectioned analysis we focused on the early Neolithic site of Mehrgarh in Pakistan where labial/buccal wear is found in mostly older adult males. We studied 215 teeth from ten individuals from the site. From the literature and some personal observations, we review evidence from the Czech early Upper Paleolithic and many later sites in the Old and New Worlds. Results. For Mehrgarh macroscopic observations revealed numerous teeth with labial and buccal facets affecting nearly every tooth class. Binocular and scanning electron microscopy and one thin-sectioned tooth provided detailed information about the wear characteristics on the facets. Comparisons. The most striking parallels to wear at Mehrgarh come from recent Inuit and Northwest Coast Native Americans where labret use was frequent in males and females. Vestibular wear occurs in a wide variety of specimens from the early Upper Paleolithic to modern patients. Unlike Mehrgarh and earlier prehistoric groups, in many cases Native American teeth are associated with the actual labrets in the graves. Conclusion. Occlusal wear or attrition caused by dental/oral manipulations where the teeth were used as tools is different, based on the resultant facets left on the teeth and micro-wear features. In prehistoric Europe, labret use extends back, at least, to the early Upper Paleolithic. As in recent humans, the use of labrets in prehistoric groups likely represents personal adornment tied to concepts of beauty and/or achieved/acquired status.